2009
DOI: 10.1515/bc.2009.052
|View full text |Cite
|
Sign up to set email alerts
|

Management of the human mucosal defensive barrier: evidence for glycan legislation

Abstract: The human gastrointestinal barrier comprises several layers which enable protection against the external environment. The mucosal epithelium, lamina propria, glycocalyx and secreted mucus each make a contribution to barrier protection. Glycocalyx and secreted mucins constitute a glycosylated environment which interacts with the enteric microflora. Turnover of the mucus layer and the creation of binding ligands for bacteria are significant factors in gut homeostasis. The gut microbiota is composed of many bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 97 publications
0
33
0
Order By: Relevance
“…Based on biochemical characterisation, nineteen genes are currently assigned to the mucin family (see [337,338]) and are named "MUCnumber" for humans or "Muc-number" for other species [112]. Mucin genes typically possess repetitive region/s which is/are the sites where glycosylation takes place [339].…”
Section: Genetic Studies In Fish Skinmentioning
confidence: 99%
“…Based on biochemical characterisation, nineteen genes are currently assigned to the mucin family (see [337,338]) and are named "MUCnumber" for humans or "Muc-number" for other species [112]. Mucin genes typically possess repetitive region/s which is/are the sites where glycosylation takes place [339].…”
Section: Genetic Studies In Fish Skinmentioning
confidence: 99%
“…24 This ''sugary'' layer mediates cell-cell recognition, receptor-ligand interactions, and adds to the barrier function of the plasma membrane, as best characterized for the endothelial 25 and intestinal glycocalyx. [26][27][28] This juxtamembranous layer may locally alter the pH near, but exterior, to the lipid bilayer. In melanoma cells, the pH measured in the glycocalyx was reported to be slightly higher than the pH of the medium, and the absolute number of H þ molecules differed up to 40% between different domains of the glycocalyx of a single cell.…”
mentioning
confidence: 99%
“…Often a necessary precondition for colonization of the human gastrointestinal (GI) tract by probiotic bacteria is preferential adherence to the intestinal mucosa, which in turn prolongs and stabilizes intestinal residence, possibly triggering a variety of defensive host cell immune responses and excluding pathogenic bacteria by competitive inhibition or steric hindrance (48). The outermost layer of the intestinal mucosa, which is a secreted and hydrated mucus gel that acts as a protective barrier and filter, consists primarily of a heterogeneous mixture of highly glycosylated membrane-associated and secreted glycoproteins called mucins (36). Although many studies have demonstrated that various probiotic Lactobacillus spp.…”
mentioning
confidence: 99%